Healthy Living: Change Your Lifestyle Word Scramble - Valerie Weyenberg; Karla P. Shelnutt (EDIS)
FCS8894, a one-page illustrated handout by Valerie Weyenberg and Karla P. Shelnutt, provides an activity to familiarize program participants with lifestyle changes that can help prevent high blood pressure. Published by the UF Department of Family Youth and Community Sciences, January 2010.